PENGARUH INTENSITAS ASET TETAP, INTENSITAS MODAL, UKURAN PERUSAHAAN, DAN PERTUMBUHAN PENJUALAN TERHADAP PENGHINDARAN PAJAK - Febriansyah, Farhan; Azzahra , Sherina Fatimah; Mayangsari, Ak.,M.Si., Dr. Sekar (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Tax avoidance remains a prevalent concern for both scholars and practitioners, prompting extensive research into its determinants within corporate environments.This research aims to analyze the influence of Fixed Asset Intensity, Capital Intensity, Company Size, and Sales Growth on Tax Avoidance in companies. Fixed Asset Intensity is measured as the proportion of fixed assets to total assets, while Capital Intensity is measured as the proportion of capital to total assets. Company size is measured based on total company assets, and Sales Growth is measured based on annual sales growth. The data used are secondary data taken from financial reports and company sustainability reports. The sampling technique used is purposive sampling, which sample size of 27 companies listed on the Indonesia Stock Exchange from 2021 to 2023. The total sample used were 105 companies from finance sector that revealed complete financial reports from 2021 to 2023, we employ Data analysis techniques used descriptive statistical tests and multiple regression tests with the Statistical Package For Social Science (SPSS). to analyze the relationships between these variables. The research results show that Fixed Asset Intensity has a significant negative effect on Tax Avoidance, which shows that companies with a higher proportion of fixed assets tend to have lower tax avoidance. On the other hand, Capital Intensity and Company Size have a significant positive influence on Tax Avoidance, which shows that companies with a higher proportion of capital and larger size tend to engage in higher tax avoidance. However, Sales Growth does not show a significant influence on Tax Avoidance. These findings provide important implications for regulators and policy makers to consider these factors in developing more effective and fair tax policies. Apart from that, this research also provides insight for company management regarding the factors that can influence their decisions regarding tax avoidance.